Bachelard, une éducation à la science et à la poétique - Perru, Olivier (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2023)
We can affirm that Gaston Bachelard’s thinking emerged from an idealistic philosophy, based on the thinking subject, in order to restore an analogical vision of the relationship to objects, a vision very much centered on matter—whether it be through a scientific approach or an imaginary-poetic approach. But an underlying dimension of this work, and related to the two previous ones, is that of education. On the epistemological level, Bachelard proposes a research approach, non-dogmatic, and anti-Cartesian; he is wary of what has been learned in science; he values experimentation provided that it is framed by theory and scientific reasoning. He insists on the purification of the scientific imagination in order to avoid epistemological obstacles, to overcome them through an objectification that is truly realized in abstraction. Symbolically, however, Bachelard restores all their importance to the qualities and elements of the physical world which he had had to eliminate from the scientific process. The abstraction of the scientific approach is not enough to understand our environment, so here we must return to the concrete, natural experience, linked to human experience and the physical world. It is necessary to intellectually integrate our gaze on the beauty and qualities of nature. This means supplementing scientific training with literary and artistic training which shows that another view of the world is possible.